2015
DOI: 10.13187/ejmb.2015.10.188
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Titanium Dioxide Nanoparticles on Salivary Alkaline Phosphatase Activity

Abstract: The structural and optical properties of the titanium dioxide nanoparticles [TiO2 NPs] have been investigated using [UV-Vis] spectrophotometer and SEM. The produced nanoparticles show small and about sharp round peaks around 220 nm. The produced nanoparticles have a spherical shape with an average particle size ˂50 nm. The effect of titanium dioxide NPs was studied on the activity of Alkaline Phosphatase [ALP] in the saliva of 25 patients with gingivitis in comparison to 20 healthy subjects with the average ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The chemical evaluation revealed that TiO2 NPs caused an elevation in peroxidase activity. Al-Rubaee et al in 2016 showed that Total salivary peroxidase was activated significantly (p˂0.001) by TiO2 NPs 13 . The surface of the nanoparticles can cause changes in the form of the protein when it attaches itself to the nanoparticle surface.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical evaluation revealed that TiO2 NPs caused an elevation in peroxidase activity. Al-Rubaee et al in 2016 showed that Total salivary peroxidase was activated significantly (p˂0.001) by TiO2 NPs 13 . The surface of the nanoparticles can cause changes in the form of the protein when it attaches itself to the nanoparticle surface.…”
Section: Discussionmentioning
confidence: 99%
“…In another similar study, to determine the effect of TiO 2 nanoparticles on the activity of salivary ALP enzyme in individuals with gingivitis, it was found that the TiO 2 NPs caused inhibition of the salivary ALP activity at lower concentrations more than the higher range of concentrations. 18 In kinetic study on the action of TiO 2 NPs on the enzymatic activity of salivary peroxidase, salivary peroxidase was found to be activated by TiO 2 NPs. 31 A study on the effect of zinc oxide NPs (ZnO NPs) on the enzymatic activity of salivary ALP in chronic periodontitis patients showed that ZnO NPs caused an increase in the salivary ALP activity.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with the results of other studies that revealed an increase of activity of salivary ALP in patients with chronic periodontitis compared to gingivitis or healthy individuals. [18][19][20] This can be explained as due to the release of the enzyme by bacterial cells and inflammatory cells. 21 ALP is released by secondary granules of neutrophils and its concentration increases greatly with an increase in inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques such as naked eyes and ultraviolet–visible spectroscopy (UV-vis) have been used with different materials in detection ALP. For example, AL-Rubaee et al (2015) used UV-vis spectroscopy in a developed platform for ALP detection in saliva-based on titanium dioxide NPs (TiO 2 NPs) [149]. Findings from the study showed that the technique could be applied in sensitive and selective detection of ALPs in patients with gingivitis.…”
Section: Recent Technologymentioning
confidence: 99%